Plants on duty – phytotechnologies and phytoremediation at a glance - Oleksińska, Zuzanna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2015)
Phytotechnologies are plant based technologies of remediation and containment of pollutions. Many advantages of phytotechnologies such as control of water and biogeochemical cycles, positive impact on soil characteristics and lowering the risk of erosion, contaminant immobilization and destruction, habitat restoration, low costs of implementation, and high public acceptance, decide that in more and more cases it is a preferred and recommended method of rehabilitation. Vegetation selected to the particular site conditions and having required characteristics will shape other biotic communities. It is thus immensely important to gather detailed knowledge about all the elements and processes occurring at the place of interest, before employing adequate phytotechnology application.